Application Of Alternative Food-Preservation Technologies To Enhance Food Safety And Stability - Bevilacqua, Antonio; Rosaria, Maria; Sinigaglia, Milena (Bentham Science Publishers, 2010)
The book covers the applications of some alternative approaches for prolonging food shelf life. The book describes the role of food safety objectives, natural compounds (such as oils and microbial enzymes), pressure and atmospheric techniques and alternative approaches (microwave, irradiation and mathematical microbial modeling) in food preservation.Implications of preservative approaches on food texture and sensorial quality are also discussed along with technology related hurdles commonly encountered in the field. The book should be very useful for food producers and microbiologists.